Improving Literacy through Reading Guide Learning Methods in Elementary School Students - Moh. Toharudin; Daniar Rahmah Dinita; Rila Melyana Fitri; Annisa Loyla Nuzralita (PT FORMOSA CENDEKIA GLOBAL, 2023)
Re-education seeks to encourage the progress of student literacy in Indonesia. The purpose of this study was to determine the increase in the results of students' reading literacy tests after carrying out learning using the reading guide learning method for students in grade 4 SDN Klampis 02 Brebes